Evaluation of serum zonulin and occludin levels in obsessive-compulsive disorder and the effect of major depressive disorder comorbidity - Zengil, Sertaç; Laloğlu, Esra (Frontiers in Psychiatry, 2024)
The aim of this study is to determine whether the levels of zonulin and occludin, tight junctions (TJ) proteins in the intestinal epithelium, will differ between obsessive compulsive disorder (OCD) patients and healthy controls. We also intended to investigate whether these would vary in OCD patients with and without major depressive disorder (MDD) comorbidity and in comparison with healthy controls.Methods: Sixty patients diagnosed with OCD and 30 healthy controls were included in the study. The cases were administered the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) and the Hamilton Depression Rating Scale (HDRS). The patients were divided into two subgroups based on their HDRS scores and presence of MDD comorbidity. Zonulin and occludin levels were measured using the ELISA method. The research was carried out between April 2021 and October 2021.Results: Zonulin and occludin levels were significantly higher in the OCD patient group than in the control group (p<0.001). The levels of both were also significantly higher in the OCD patients with MDD comorbidity (OCD+MDD) compared to those without MDD (OCD-MDD) (p<0.001). Zonulin and occludin levels also rose significantly as disease severity increased in the OCD patient group (respectively; p<0.001, p=0.001). The levels of both increased in line with the severity of depression based on HDRS scores in the OCD+MDD group (p<0.001). A positive correlation was determined between the duration of OCD and zonulin and occludin levels. Evaluation of the entire OCD group revealed a moderate positive correlation between Y-BOCS and HDRS scores and zonulin and occludin.Conclusions: Zonulin and occludin levels in this research were significantly higher in the patients with OCD than in the healthy controls. That elevation was positively correlated with disease duration and severity, and the increase was significantly more pronounced in OCD with MDD comorbidity. These findings point to a possible disorder in the intestinal barrier and blood-brain barrier in OCD patients.